Losing Face and Sinking Costs: Experimental Evidence on the Judgment of Political and Military Leaders. (20th May 2015) - Renshon, Jonathan
Abstract: Status has long been implicated as a critical value of states and leaders in international politics. However, decades of research on the link between status and conflict have yielded divergent findings, and little evidence of a causal relationship. I attempt to resolve this impasse by shifting the focus from status to relative status concerns in building a theory of status from the ground up, beginning with its behavioral microfoundations. I build on and extend previous work through an experimental study of status threats and the escalation of commitment, operationalized here as a new behavioral escalation task using real financial incentives and framed around a narrative of war and peace. I utilize a unique sample of high-profile political and military leaders from the Senior Executive Fellow (SEF) program at the Harvard Kennedy School, as well as a group of demographically matched control subjects, allowing me to evaluate the moderating effect of power on status concerns while also addressing typical concerns about external validity in IR experiments. I find strong evidence that the fear of losing status impedes decision making and increases the tendency to "throw good money after bad, " but that power aids decision making by buffering high-power subjects against the worst effects of status loss.